Can Africa claim the 21st century? - Gelb, Alan H.; World Bank. (Washington, D.C. : World Bank, 2000)
This volume argues for a better and more effective compact among Africa and its development partners. It is a product of the increasing spirit of collaboration among some of the major institutions involved in African development.
"joint product of five collaborating institutions, represented by a Steering Committee coordinated by Alan Gelb"--P. xii.
Includes bibliographical references (p. 259-278).
oif 27/04/15
Loan
Keywords: Social change; Poverty; Equality; Infrastructure (Economics); Africa